KOMPETENSI GURU PAUD DI BANJARMASIN YANG TIDAK MEMILIKI LATAR BELAKANG PENDIDIKAN S1 PAUD - Az-Zahra, Wafiqa; Koenarso, Dyah Ageng Pramesty; Yarliani, Ikta (Titik Fokus Karya, 2024)
Teachers have abilities that play an important role in carrying out their duties, and their level of competence often determines the success of education. In an effort to meet competency standards, teachers are expected to have the knowledge and skills appropriate to their field. However, there are still gaps in this regard, especially in aspects such as pedagogic, professional, personal and social competencies. Therefore, this study aims to evaluate the competencies of PAUD teachers who are not S1 PAUD education graduates in two institutions in Banjarmasin City, as well as identify factors that influence their competencies. This study used a descriptive qualitative approach, with data collection through observation, interviews and documentation. The results showed that some teachers still face difficulties in preparing lesson plans independently, which has an impact on the monotony of the learning process. In addition, there are teachers who have not fully fulfilled aspects of social competence.